Computer-aided dosage in oral anticoagulation therapy using phenprocoumon - Cromme, L.; Völler, H.; Gäbler, F.; Salzwedel, A.; Taborski, U. (Hämostaseologie, 2010)
Oral anticoagulation using vitamin K antagonists has been established for over 50 years. Although it is highly effective in preventing thromboembolic incidents, its therapeutic control still remains problematic. Therefore, a computer-aided approach is recommended for deriving dosages. Up to now, the dosage is often based on the visual inspection of previous INR measurements, average weekly doses, and the INR target range. Statistical variations of measurement results and time-delayed effects of dosages, however, frequently result in the misinterpretation of data and suggest pseudo-trends. Treating physicians are not only responsible for determining the patient-specific maintenance dose, but must also respond to deviating INR values, overdosage or underdosage, initiate the oral anticoagulation therapy, and control the INR level in case of a new target range (bridging). Instructive examples are provided to illustrate the described difficulties.A computer-aided expert system is currently developed to ensure the therapeutic safety under the specified conditions. We present preliminary results from a study designed to validate mathematical models underlying such expert systems.
Keywords: Oral anticoagulation; phenprocoumon; dosage; computer-aided expert system; mathematical models in anticoagulation therapy